Nanomolar Clodronate Induces Adenosine Accumulation in the Perfused Rat Mesenteric Bed and Mesentery-Derived Endothelial Cells - Garcia Huidobro-Toro, J; Barra-Pezo, R; Donoso-Gomien, M (Frontiers Media S.A., 2023)
The vesicular nucleotide transporter (VNUT) is critical for sympathetic co-transmission and purinergic transmission maintenance. To examine this proposal, we assessed whether the bisphosphonate clodronate, claimed as a potent in vitro VNUT blocker, modified spontaneous and/or the electrically evoked overflow of ATP/metabolites and NA from mesentery sympathetic perivascular nerve terminals. Additionally, in primary endothelial cell cultures derived from this tissue, we also evaluated whether clodronate interfered with ATP/metabolite cell outflow and metabolism of N6-etheno adenosine 5′-triphosphate (eATP), N6-etheno adenosine (eADO), and adenosine deaminase enzyme activity. Rat mesenteries were perfused in the absence or presence of.01–1,000 nM clodronate, 1–1,000 nM Evans blue (EB), and 1–10 µM DIDS; tissue perfusates were collected to determine ATP/metabolites and NA before, during, and after perivascular electrical nerve terminal depolarization. An amount of 1–1,000 nM clodronate did not modify the time course of ATP or NA overflow elicited by nerve terminal depolarization, and only 10 nM clodronate significantly augmented perfusate adenosine. Electrical nerve terminal stimulation increased tissue perfusion pressure that was significantly reduced only by 10 nM clodronate [90.0 ± 18.6 (n = 8) to 35.0 ± 10.4 (n = 7), p =.0277]. As controls, EB, DIDS, or reserpine treatment reduced the overflow of ATP/metabolites and NA in a concentration-dependent manner elicited by nerve terminal depolarization. Moreover, mechanical stimulation of primary endothelial cell cultures from the rat mesentery added with 10 or 100 nM clodronate increased adenosine in the cell media. eATP was metabolized by endothelial cells to the same extent with and without 1–1,000 nM clodronate, suggesting the bisphosphonate did not interfere with nucleotide ectoenzyme metabolism. In contrast, extracellular eADO remained intact, indicating that this nucleoside is neither metabolized nor transported intracellularly. Furthermore, only 10 nM clodronate inhibited (15.5%) adenosine metabolism to inosine in endothelial cells as well as in a commercial crude adenosine deaminase enzyme preparation (12.7%), and both effects proved the significance (p <.05). Altogether, present data allow inferring that clodronate inhibits adenosine deaminase activity in isolated endothelial cells as in a crude extract preparation, a finding that may account for adenosine accumulation following clodronate mesentery perfusion. Copyright © 2023 Donoso, Hernández, Barra and Huidobro-Toro.